2020
DOI: 10.1111/acel.13120
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in the nutritional requirement for adult lifespan in Drosophila melanogaster

Abstract: The nutritional requirements of Drosophila have mostly been studied for development and reproduction, but the minimal requirements for adult male and female flies for lifespan have not been established. Following development on a complete diet, we find substantial sex difference in the basic nutritional requirement of adult flies for full length of life. Relative to females, males require less of each nutrient, and for some nutrients that are essential for development, adult males have no requirement at all fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 42 publications
9
37
0
Order By: Relevance
“…This approach is the opposite of, but complementary to, the already recognised strategies to extend lifespan by DR, which reduce maternal investment into reproduction by decreasing the dietary protein : carbohydrate ratio (Mair et al, 2005;Lee et al, 2008;Skorupa et al, 2008) or by treating the animals with rapamycin that suppresses TOR and reduces reproduction (Bjedov et al, 2010;Harrison et al, 2009;Liu & Sabatini, 2020). It is also consistent with our recent work that showed non-reproducing adult males and genetically sterile females suffer little to no lifespan cost when sterol deprived, which is presumably because they conserve sterols which would otherwise be depleted by reproduction (Wu et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This approach is the opposite of, but complementary to, the already recognised strategies to extend lifespan by DR, which reduce maternal investment into reproduction by decreasing the dietary protein : carbohydrate ratio (Mair et al, 2005;Lee et al, 2008;Skorupa et al, 2008) or by treating the animals with rapamycin that suppresses TOR and reduces reproduction (Bjedov et al, 2010;Harrison et al, 2009;Liu & Sabatini, 2020). It is also consistent with our recent work that showed non-reproducing adult males and genetically sterile females suffer little to no lifespan cost when sterol deprived, which is presumably because they conserve sterols which would otherwise be depleted by reproduction (Wu et al, 2020).…”
Section: Discussionsupporting
confidence: 89%
“…In mechanistic work, the increased lifespan under dietary restriction has been attributed to the benefits of reduced dietary protein, which enhances proteome maintenance via reduced TOR signalling (Harrison et al, 2009;Partridge et al, 2011;Kapahi et al, 2017;Piper et al, 2017;Sabatini, 2017;Dobson et al, 2018;Liu & Sabatini, 2020). However, we have shown that flies on a high protein : carbohydrate diet, in which TOR signalling would be expected to remain high, can still sustain a long lifespan if supplemented with cholesterol, or alternatively, if the cost of reproduction on sterol stores is removed by making flies infertile (Wu et al, 2020). This demonstrates that the major improvement to lifespan observed on low protein diets is not the result of enhanced proteostasis, but is instead, a side effect of avoiding sterol depletion caused by egg production.…”
Section: Extending Fly Lifespan By Dr Involves An Indirect Trade-offmentioning
confidence: 91%
See 2 more Smart Citations
“…Therefore, the increased levels of BAs and taurine in the intestine during CR could contribute to the previously described phenotype. Importantly, taurine supplementation, similary like CR has been shown to reduce endoplasmic reticulum stress and extend lifespan in C. elegans (Kim et al, 2010, Wu et al, 2020). Consequently, taurine has already been suggested as a supplement mimicking beneficial outcomes of CR (Nishizono et al, 2017).…”
Section: Discussionmentioning
confidence: 99%